Investigation of active interface control of pressure driven two-fluid flow in microchannels - Wang, Cheng (2012)
We report a novel concept to control the interface location of a pressure-driven multi-phase flow in a microchannel by using electroosmotic flow effects. This concept has potential applications in flow switching and cell sorting in bio-analytical systems. In an H-shaped microchannel structure, aqueous sodium chloride (NaCl) solution and glycerol diluted with water were pumped through two inlets at the same flow rate. The electric field was applied on the electrolyte solution side. Adjusting the magnitude and direction of electric field has successfully controlled the interface position between the two phases. This technique provides a new approach to control the interface position between the two fluids.